Uncovering the declining communist threat in Singapore from 1959-1989 - Devan, Darien Zhe Yuan (Nanyang Technological University, 2022)
Before being granted limited self-governance in 1959, the Singapore colonial government was already facing a growing communist threat as seen in the first Malayan Emergency from 1948 to 1960. But the Communists began to change their modus operandi from an armed struggle towards an “open united front” from 1954 to 1966. Their focus was to rebuild their support base and forces as they had lost much of their forces in the Japanese Occupation and the Malayan Emergency. This shifted their strategy from forcefully taking power through direct conflict towards subversive activities with the goal of gaining popular support on the ground by winning the hearts and minds of Singaporeans. This paper aims to address the various factors which resulted in the Communists’ eventual dissolution.